Parascientific revolutions: the science and culture of the paranormal - Lee, Derek (Proximities, 2025)
"What can an exploration of pseudoscientific phenomena like telepathy, clairvoyance, precognition, and telekinesis tell us about accepted scientific and cultural thought? Examining how ideas rejected by the scientific establishment regenerate and return to mainstream discourse, Parascientific Revolutions offers fresh insight into how the paranormal mind continually challenges our understanding of knowledge and belief"-- Provided by publisher